Students and Management Perspective on Service Quality and Integrated Marketing Communication: Descriptive Analysis on Indonesian Private Universities - Junaid Ali Saeed Rana; Antonius Agus Susanto; Wenny Chandra Mandagie (International Journal of Digital Entrepreneurship and Business, 2021)
To formulate aggressive marketing strategies, the quality of service and marketing communication tools must provide a meaningful and consistent message. Service quality is gaining substantial respect in service marketing literature and higher education services. Aggressive marketing strategies among private universities have enabled these institutes to become marketing-oriented as students are considered consumers, therefore universities can expand their marketing efforts through improved service quality and consistent marketing communication in the form of Integrated Marketing Communication. This paper provides multiple-perspective (staff and student) descriptive analysis in evaluating service quality along with the importance of integrated marketing communication. The data from 34 universities (management perspective) and 5 large-sized universities (student perspective) was collected, analyzed, and compared using meaningful graphs providing significant conclusions. The paper concludes by providing suggestions, to private universities in Indonesia to efficiently and effectively incorporate service quality and integrated marketing communication in their action plans to improve their ranking and services that they promise to provide their current and prospective students.